PENGARUH TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE DAN PERSEPSI PROFESI GURU TERHADAP KESIAPAN MENJADI GURU - Nabila, Alma; Solihat, Ai Nur; Gumilar, Gugum (Transpublika Publisher, 2023)
This study aims to determine the effect Of Technological Pedagogical Content Knowledge and Perceptions Of The Teaching Profession on The Readiness To Become A Prospective Teacher of economics at Siliwangi University. The research method used is descriptive correlational. The sample in the research was students majoring in Economics Education Batch 2020 and 2021, totaling 138 students. The sampling technique used is the proportionate random sampling technique or proportional random samples. Data collection techniques in this study using a questionnaire. This study conducted a hypothesis test, namely multiple linear regression tests. The results of the study show that: 1) There is an influence of Technological Pedagogical Content Knowledge on Teacher Readiness, with a significant t value of 0.001 and a t statistic of 3,482. 2) There is an influence of the Perception Of The Teaching Profession on Readiness To Become A Teacher, with a significant t of 0.007 and a t statistic of 2,738. 3) There is a significant influence between Technological Pedagogical Content Knowledge and Perceptions Of The Teaching Profession on Readiness To Become A Teacher, with a calculated F value of 7,082 with an F significance value of 0.001.